Importance of sensory evaluation in assessment of egg quality - Margeta, Polona; Kralik, Gordana; Grčević, Manuela; Hanžek, Danica; Kralik, Zlata (2019)
The sensory evaluation is a scientific discipline used to evoke, measure, analyze and interpret reactions to stimuli perceived through senses of sight, smell, touch, taste, and hearing. Sensory evaluation applies principles of experimental design and statistical analysis to the use of human senses aiming to isolate the sensory properties of foods themselves and provide important and useful information to product developers, food scientists, and managers about the sensory characteristics of food products. To achieve the scientific control of the sensory evaluation test, good laboratory practice should be applied. It includes defining the test objective and test type, selection of right assessors, ensuring right test area, handling and preparing the sample in appropriate way, paying attention to test set-up and storing the test data safe in logical order. Regarding eggs, sensory characteristics are usually evaluated on eggs enriched with bioactive compounds. Sensory studies are often conducted either with trained (in accordance with international reference standards) or untrained panelists. Sensory evaluation of eggs after addition of different compounds is of great importance because sensory attributes such as aroma, flavor, aftertaste and overall acceptability of enriched eggs are very important to consumers.
Senzorna procjena je znanstvena disciplina koja se koristi za evociranje, mjerenje, analizu i tumačenje reakcija na podražaje koji se percipiraju kroz osjetila vida, mirisa, dodira, okusa i sluha. Senzorna procjena primjenjuje načela eksperimentalnoga oblikovanja i statističke analize za korištenje ljudskih osjetila u pokušaju izoliranja osjetilnih svojstava hrane i daje važne i korisne informacije proizvođačima, znanstvenicima koji se bave hranom te menadžerima o osjetilnim karakteristikama prehrambenih proizvoda. Da bi se postigla znanstvena kontrola senzornoga testa procjene, potrebno je primijeniti dobru laboratorijsku praksu, koja uključuje definiranje cilja i tipa ispitivanja, odabir pravih procjenitelja, osiguravanje odgovarajućega područja ispitivanja, rukovanje i pripremanje uzorka na odgovarajući način, vodeći računa o tome da je postavljanje ispitivanja i pohranjivanje podataka ispitivanja sigurno i u logičkom redoslijedu. Kada se radi o jajima, osjetilna svojstva obično se procjenjuju na jajima obogaćenim bioaktivnim spojevima. Senzorne studije često se (u skladu s međunarodnim referentnim standardima) provode s obučenim ili neobučenim panelistima. Senzorna procjena jaja nakon dodavanja različitih spojeva od izuzetne je važnosti, jer su senzorna obilježja, kao što su aroma, okus, naknadni okus i sveukupna prihvatljivost obogaćenih jaja, vrlo važna potrošačima.
Bibliografija: 36 jed.
Summary ; Sažetak.
Keywords: Jaja -- Senzorna procjena -- Obogaćivanje hrane -- Kvaliteta jaja